Nanoplasmonic near-field synthesis - Feist, Johannes; Reid, M. T. Homer; Kling, Matthias F. (My University, 2013)
The temporal response of resonances in nanoplasmonic structures typically converts an incoming few-cycle field into a much longer near-field at the spot where nonlinear physical phenomena including electron emission, recollision, and high-harmonic generation can take place. We show that for practically useful structures pulse shaping of the incoming pulse can be used to synthesize the plasmon-enhanced field and enable single-cycle-driven nonlinear physical phenomena. Our method is demonstrated for the generation of an isolated attosecond pulse by plasmon-enhanced high harmonic generation. We furthermore show that optimal control techniques can be used even if the response of the plasmonic structure is not known a priori.